Sociocultural transformations as an influence on the loss of parental authority - Fajardo Romero, Claudia Lorena (2018)
This article addresses the analysis of the results obtained from the exploratory research conducted during the academic training, which had as objective to distinguish how sociocultural transformations influence on roles changing and the exercise of the authority in families, from teachers’ professional perspective and parents belonging to Nuevo Compartir School from comuna 1 of Soacha Municipality. It was observed a transformation in parental authority that come from a historical evolution, in terms of the society’s behavior and the different perspectives that are immersed in the social role of each individual, breaking with the traditional paradigm of a patriarchal role, and thus giving way to new paradigms that are linked with social, technological, legal and ideological changes that foster a change in family roles and dynamics.   DOI: https://doi.org/10.31876/sl.v1i1.32